Therapeutic Strategies and Metal-Induced Oxidative Stress: Application of Synchrotron Radiation Microbeam to Amyotrophic Lateral Sclerosis in the Kii Peninsula of Japan - Yoshida, Sohei (Frontiers in Neurology, 2022)
A series of extensive gene-environment studies on amyotrophic lateral sclerosis (ALS) and Parkinsonism-dementia complex (PDC) in Guam, USA and the Kii Peninsula of Japan have led us to hypothesize that a prolonged low Ca and Mg intake may cause oxidative stress to motor and nigral neurons by an increased uptake of environment metallic elements, i.e., Al, Mn and Fe. Otherwise, 5-10% of total ALS cases are familial ALS (fALS), of which 20% of the fALS cases linked to a point mutation of Cu/Zn superoxide dismutase (SOD1). In the vicinity of the Kii Peninsula, about 7% of the ALS cases are linked to the SOD1 mutation. Using synchrotron radiation (SR) micro beam, conglomerate inclusions (SOD1 aggregates) within a motor neuron of the fALS case in the vicinity revealed a loss of Cu in contrast to extremely high contents of Zn and Ca, indicating abnormalities of the active site of SOD1 protein of the fALS case. Furthermore, sALS in the Kii Peninsula showed a low Cu/Zn ratio within a motor neuron, suggesting a fragility of SOD1 proteins. From the perspective of gene-environment interactions, the above two research trends may show a common oxidative stress underlaying the neurodegeneration of Kii and Guam ALS/PDC. Therefore, it is a crucial point for the therapeutic strategy to clarify a role of transition metals in the oxidative process in both ALS/PDC, including Guam ALS and elsewhere in the world. This paper reviews a history of the genetic epidemiological studies on the clustering or disappearance of ALS/PDC of the Kii and Guam foci and the results of analytical studies on transition metals within a neuron of both sALS and fALS, especially using a synchrotron radiation (SR) micro beam of Spring-8 and Photon Factory of Japan. These researches will provide a valuable information about the oxidative stress of environmental minerals involved in neuronal cell death. To elucidate the physicochemical mechanism of the oxidative stress in neurodegeneration, it will shed a new light on the therapeutic strategies for ALS/PDC in near future.